2023
DOI: 10.2109/jcersj2.22112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stoichiometric hydroxyapatite nanoparticles via aqueous solution-precipitation at 37 °C

Abstract: Stoichiometric hydroxyapatite (HAp) nanoparticles were prepared by the solution-precipitation method at 37 °C. During the 72-h maturation period, the Ca/P molar ratio first rapidly increased to >1.6, and then reached 1.67 relatively slowly. The crystallite sizes of the stoichiometric HAp nanoparticles were estimated to be 11.0(3) and 25.7(3) nm from 300 and 002 diffractions, respectively. The crystallite size in the [001] direction continued to increase after the 72-h maturation period at a constant Ca/P molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The crystallite sizes of the calcined HAp synthesized in this study were smaller than those reported in previous studies. 11) This was due to the difference in the initial crystallite sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The crystallite sizes of the calcined HAp synthesized in this study were smaller than those reported in previous studies. 11) This was due to the difference in the initial crystallite sizes.…”
Section: Resultsmentioning
confidence: 99%